Electrostatic chuck device
The electrostatic chuck device with a MMC base and adhesive layer with high filler content addresses thermal stress and peeling issues, ensuring uniform temperature distribution and efficient cooling in semiconductor manufacturing.
Patent Information
- Application Number
- JP2023114086
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-24
AI Technical Summary
Existing electrostatic chuck devices face damage and interface peeling due to high temperatures and thermal stress from the difference in heat expansion coefficients between ceramic electrostatic chuck members and metal bases, particularly in semiconductor manufacturing processes.
An electrostatic chuck device using a metal base composite material (MMC) with a ceramic electrostatic chuck member, an adhesive layer containing a high filler content and spherical conductive fillers, and a primer layer to reduce thermal stress and improve thermal conductivity.
The device effectively reduces thermal stress and maintains uniform temperature distribution by minimizing the difference in thermal expansion coefficients, preventing damage and peeling, and enhancing heat transfer and cooling efficiency.
Smart Images

Figure 2025011772000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrostatic chuck device. [Background technology]
[0002] Conventionally, in the semiconductor manufacturing process for manufacturing semiconductors such as ICs, LSIs, and VLSIs, an electrostatic chuck device is used to electrostatically attract a plate-shaped sample such as a silicon wafer during plasma processing. The temperature distribution of the plate-shaped sample held by the electrostatic chuck device is controlled uniformly during processing so that the processing state of the plate-shaped sample during plasma processing is not uneven.
[0003] In recent years, with the diversification of semiconductor processes, the temperature of a plate-shaped sample during processing is controlled over a wider temperature range than in the past, and therefore the electrostatic chuck device is exposed to a thermal cycle over a wider temperature range than in the past.
[0004] In view of this, an electrostatic chuck device has been proposed that has an electrostatic chuck member made of ceramics and a base made of a metal matrix composite (MMC), which is a composite material of metal and ceramics (see, for example, Patent Document 1).
[0005] In the electrostatic chuck device described in Patent Document 1, the electrostatic chuck member and the base are joined by using a metal brazing material. In the electrostatic chuck device described in Patent Document 1, the amount of metal in the MMC that is the material of the base is adjusted to reduce the thermal expansion difference with the ceramic plate to below a standard level, thereby mitigating the thermal stress during brazing. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 11-163109 Summary of the Invention [Problem to be solved by the invention]
[0007] When brazing a ceramic electrostatic chuck member to an MMC base, the electrostatic chuck member and the base are exposed to high temperatures (e.g., 500°C or higher) that melt the brazing material, and there is a risk of damage due to thermal load.
[0008] Furthermore, when an electrostatic chuck device in which an electrostatic chuck member and a base are brazed together is heated in a plasma process, internal stress is generated due to differences in the thermal expansion coefficients of the electrostatic chuck member, the base, and the brazing material, which may result in damage such as interfacial peeling.
[0009] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a novel electrostatic chuck device that uses a base made of MMC. [Means for solving the problem]
[0010] [1] An electrostatic chuck device comprising: an electrostatic chuck member made of a ceramic material; a base made of a metal-matrix composite material; and an adhesive layer that bonds the electrostatic chuck member and the base, wherein the adhesive layer contains a resin material and a thermally conductive filler, wherein an absolute value of a difference in thermal expansion coefficient between the ceramic material and the metal-matrix composite material is 10 ppm / K or less, and a content of the thermally conductive filler in the adhesive layer is 50 mass % or more and 80 mass % or less.
[0011] [2] The electrostatic chuck device according to [1], wherein the thermally conductive filler is spherical.
[0012] [3] The electrostatic chuck device according to [1] or [2], wherein the thermally conductive filler has a bimodal particle size distribution.
[0013] [4] An electrostatic chuck device described in any one of [1] to [3], wherein the average particle diameter of the thermally conductive filler is equal to or less than 1 / 2 of the thickness of the adhesive layer.
[0014] [5] An electrostatic chuck device described in any one of [1] to [4], wherein a primer layer is formed on a surface of the base that contacts the adhesive layer, and the primer layer is made of an organosilicon compound having a functional group that reacts with the resin material and an alkoxy group.
[0015] [6] The electrostatic chuck device according to any one of [1] to [5], wherein the metal matrix composite material contains 75 volume% or more of silicon carbide and 1 volume% or more and 25 volume% or less of Al, Si, or Mg, when the entire metal matrix composite material is taken as 100 volume%. Effect of the Invention
[0016] According to the present invention, it is possible to provide a novel electrostatic chuck device using a base made of MMC. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an electrostatic chuck device 1A according to a first embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] [First embodiment] An electrostatic chuck device according to a first embodiment of the present invention will be described below with reference to Fig. 1. In all the following drawings, the dimensions and ratios of the components are appropriately changed to make the drawings easier to understand.
[0019] 1 is a schematic cross-sectional view showing an electrostatic chuck device 1A according to a first embodiment. The electrostatic chuck device 1A includes an electrostatic chuck member 2, a base 3, an adhesive layer 4, a support plate 5, an insulator (insertion component) 23, and a power supply terminal 16. The electrostatic chuck member 2 and the base 3 are laminated together with the adhesive layer 4 interposed therebetween.
[0020] In this specification, the direction in which the electrostatic chuck member 2 and the base 3 are stacked is referred to as the stacking direction. Furthermore, the side on which the electrostatic chuck member 2 is arranged with respect to the base 3 is referred to as one side of the stacking direction, and the other side is referred to as the opposite side. In the following description, each part of the electrostatic chuck device 1A will be described with the vertical direction as the stacking direction. However, the vertical direction here is merely used to simplify the description, and does not limit the position of the electrostatic chuck device 1A during use. The upper side corresponds to one side in the stacking direction, and the lower side corresponds to the other side in the stacking direction.
[0021] (Electrostatic chuck parts) The electrostatic chuck member 2 has a dielectric substrate 11 and an adsorption electrode 13 located inside the dielectric substrate 11. A mounting surface 2a for adsorbing a wafer W is provided on the upper surface of the electrostatic chuck member 2. A focus ring surrounding the wafer W may be disposed on the outer side of the mounting surface 2a of the electrostatic chuck member 2.
[0022] The dielectric substrate 11 is made of a composite sintered body having sufficient mechanical strength and durability against corrosive gas and its plasma. As a dielectric material constituting the dielectric substrate 11, ceramics having sufficient mechanical strength and durability against corrosive gas and its plasma are preferably used.
[0023] The ceramics constituting the dielectric substrate 11 contain aluminum oxide (Al2O3) as the main component. The term "main component" refers to occupying 50% or more by volume of the whole. For example, aluminum oxide (Al2O3) sintered compact, aluminum oxide (Al2O3)-silicon carbide (SiC) composite sintered compact, etc. are preferably used. In particular, from the viewpoints of dielectric properties at high temperatures, high corrosion resistance, plasma resistance, and heat resistance, the material constituting the dielectric substrate 11 is preferably an Al2O3-SiC composite sintered compact (hereinafter, Al2O3-SiC).
[0024] The dielectric substrate 11 is a circular plate in a plan view. The dielectric substrate 11 has a mounting surface 2a on which the wafer W is mounted, and a back surface 2b facing the opposite side to the mounting surface 2a. The mounting surface 2a may have, for example, a plurality of protrusions (not shown) formed at predetermined intervals. In this case, the mounting surface 2a supports the wafer W at the tips of the plurality of protrusions.
[0025] The adsorption electrode 13 is disposed inside the dielectric substrate 11. The adsorption electrode 13 extends in a plate shape along the mounting surface 2a of the dielectric substrate 11. When a voltage is applied to the adsorption electrode 13, the adsorption electrode 13 generates an electrostatic adsorption force that holds the wafer W on the mounting surface 2a of the dielectric substrate 11. A power supply terminal 16 for applying a DC voltage to the adsorption electrode 13 is connected to the adsorption electrode 13.
[0026] The adsorption electrode 13 is composed of a composite of an insulating material and a conductive material. The insulating material contained in the adsorption electrode 13 is not particularly limited, but is preferably at least one selected from the group consisting of aluminum oxide (Al2O3), aluminum nitride (AlN), silicon nitride (Si3N4), yttrium (III) oxide (Y2O3), yttrium aluminum garnet (YAG), and SmAlO3. The conductive material contained in the adsorption electrode 13 is preferably at least one selected from the group consisting of molybdenum carbide (Mo2C), molybdenum (Mo), tungsten carbide (WC), tungsten (W), tantalum carbide (TaC), tantalum (Ta), silicon carbide (SiC), carbon black, carbon nanotubes, and carbon nanofibers.
[0027] The thickness of the electrostatic chuck member 2 is preferably 0.5 mm or more and 5 mm or less. When the thickness of the electrostatic chuck member 2 is 0.5 mm or more, the withstand voltage of the electrostatic chuck member 2 is high. Furthermore, when the thickness of the electrostatic chuck member 2 is 5 mm or less, the heat capacity of the electrostatic chuck member 2 is small, making it easier to keep the temperature of the plate-shaped sample, which is the processing object, uniform during plasma processing.
[0028] The thermal expansion coefficient of the electrostatic chuck member 2 can be approximated by the thermal expansion coefficient of the dielectric substrate 11 constituting the electrostatic chuck member 2. When the material of the dielectric substrate 11 is Al2O3-SiC, the thermal expansion coefficient of the electrostatic chuck member 2 is 7 to 8 ppm / K (@25°C to 100°C).
[0029] (Base) The base 3 supports the electrostatic chuck member 2 from below. The base 3 is provided with a support surface 3a facing upward and a lower surface 3b facing downward. The support surface 3a faces the rear surface 2b of the dielectric substrate 11 in the vertical direction via an adhesive layer 4. The base 3 supports the electrostatic chuck member 2 on the support surface 3a.
[0030] A flow path 3f for circulating a coolant is provided inside the base 3. A liquid such as water or an organic solvent is used as the coolant flowing through the flow path 3f. The flow path 3f extends along the support surface 3a. The coolant in the flow path 3f cools the entire base 3 and also cools the electrostatic chuck member 2 via the support surface 3a.
[0031] The base 3 is a disk-shaped member in a plan view, and is made of a material having a thermal conductivity of 140 W / m·K or more. In this specification, the term "plan view" refers to a field of view seen from the thickness direction of the electrostatic chuck member 2.
[0032] A known metal matrix composite (hereinafter, MMC) can be used as the material for the base 3. The MMC can be prepared by a known method (metal infiltration method, forging method) in which a porous ceramic base material is prepared and then Al or Si is introduced into the pores of the ceramic base material.
[0033] More specifically, the MMC material of the base 3 preferably contains SiC as a material. More specifically, the material of the base 3 preferably contains 75 volume % or more but less than 100 volume %, and preferably 75 volume % or more and 99 volume % or less of SiC, when the entire base 3 is taken as 100 volume %. The base 3 contains one or more elements selected from the group consisting of aluminum (Al), silicon (Si) and magnesium (Mg) in addition to SiC. By containing these elements in SiC, the thermal conductivity of the base 3 is improved, and heat dissipation through the base 3 is facilitated. In a material containing 75 volume % or more of SiC as the material of the base 3, the thermal expansion coefficient can be reduced to 2.8×10 by adjusting the mating material contained in the material. -6 / K~6.8×10 -6 It can be controlled within the range of / K.
[0034] The absolute value of the difference in thermal expansion coefficient between the MMC material of the base 3 and the ceramic material of the electrostatic chuck member 2 is 10 ppm / K or less, and preferably 7.0 ppm / K or less. When the amount of agent in the base 3 and the material of the electrostatic chuck member 2 satisfy the above relationship, internal stress due to thermal deformation during heating can be easily suppressed.
[0035] The material of the base 3 is preferably a material containing 75% to 99% by volume of SiC and 1% to 25% by volume of Al, Si or Mg when the entire base 3 is taken as 100% by volume. The thermal expansion coefficient of the base 3 having such a composition is very close to that of the Al2O3-SiC constituting the electrostatic chuck member, and the difference in the amount of thermal expansion with the electrostatic chuck member 2 during heating is small.
[0036] The MMC may be, for example, Mg-SiC (7.0 ppm / K), Al-SiC (6.8 ppm / K), or Si-SiC (2.8 ppm / K). The amount of metal contained in each MMC may be adjusted appropriately within the above-mentioned content range according to the desired thermal expansion coefficient.
[0037] The surface of the base 3 is preferably covered with a metal film. For example, an Al sprayed film can be used as the metal film. The thickness of the metal film can be, for example, 100 μm or more and 300 μm or less. This allows the base 3 to be used as an internal electrode for generating plasma. The base 3 is connected to an external high-frequency power source 22 via a matching box (not shown).
[0038] The base 3 is provided with a hole 17. The hole 17 extends in the up-down direction. The hole 17 penetrates the base 3 in the up-down direction and opens to the support surface 3a and the bottom surface 3b of the base 3. The hole 17 is, for example, circular in plan view. An insulator 23, which will be described later, is inserted into the hole 17. FIG. 1 shows the hole 17 penetrating the base 3 in the up-down direction, but the hole 17 does not necessarily have to penetrate the base 3 as long as it opens at least to the support surface 3a and the insulator 23 is inserted therein.
[0039] (Adhesive layer) The adhesive layer 4 is sandwiched between the electrostatic chuck member 2 and the base 3, and bonds the electrostatic chuck member 2 and the base 3. The adhesive layer 4 contains a resin material and a thermally conductive filler (hereinafter simply referred to as a filler).
[0040] The adhesive layer 4 containing a resin material is relatively more easily deformed than the electrostatic chuck member 2 and the base 3. Therefore, compared to a joining layer formed by brazing, the adhesive layer 4 is more easily deformed when the electrostatic chuck member 2 and the base 3 expand or contract due to a temperature change. Furthermore, even if there is a difference between the amount of thermal expansion of the electrostatic chuck member 2 and the base 3, for example, the adhesive layer 4 deforms, thereby making it possible to suppress internal stress caused by the difference in the amount of thermal expansion.
[0041] The resin is not particularly limited as long as it is not likely to undergo cohesive failure due to thermal stress, and examples thereof include silicone resin, acrylic resin, epoxy resin, phenolic resin, polyurethane resin, unsaturated polyester resin, etc. Among these, silicone resin is preferred because it has a high degree of elasticity and is not likely to undergo cohesive failure due to changes in thermal stress.
[0042] The filler has a function of improving the thermal conductivity in the thickness direction of the adhesive layer 4. For this function, the filler may be one or more selected from the group consisting of inorganic oxides, inorganic nitrides, and inorganic oxynitrides. For example, the filler preferably contains surface-coated aluminum nitride (AlN) particles in which a coating layer made of silicon oxide (SiO2) or aluminum oxide (Al2O3) is formed on the surface of aluminum nitride (AlN) particles.
[0043] The filler content in the adhesive layer 4 is 50% by mass or more and 80% by mass or less. The filler content is preferably 55% by mass or more, and more preferably 60% by mass or more. The filler content is preferably 75% by mass or less, and more preferably 70% by mass or less. The upper and lower limit values of the filler content can be combined in any desired manner.
[0044] When the filler content is equal to or higher than the lower limit, sufficient thermal conductivity can be imparted to the adhesive layer 4, and heat transfer from the electrostatic chuck member 2 to the base 3 can be promoted. When the filler content is equal to or lower than the upper limit, the adhesive layer 4 is likely to deform in response to expansion or contraction of the electrostatic chuck member 2 and the base 3 due to temperature change.
[0045] When an adhesive layer containing a resin material is used, a known electrostatic chuck device employs Al as the material of the base. The base made of Al has a larger thermal expansion coefficient than the electrostatic chuck member made of ceramics, and is significantly deformed when heated. Therefore, when the electrostatic chuck member and the base thermally expand in the plasma process, the difference in the amount of thermal expansion between the electrostatic chuck member and the base is large, and there is a risk that the adhesive layer containing a resin material will break. However, since the base 3 of this embodiment is made of MMC, the difference in the amount of thermal expansion between the electrostatic chuck member 2 and the base can be reduced, and the breakage of the adhesive layer can be suppressed.
[0046] Furthermore, in the electrostatic chuck device 1A of the present embodiment, by employing the base 3 made of MMC, the amount of deformation required of the adhesive layer to absorb the thermal expansion of the electrostatic chuck member 2 and the base 3 can be smaller than in an electrostatic chuck device employing an Al base. Therefore, compared to an electrostatic chuck device employing an Al base, the amount of filler contained in the adhesive layer can be increased to 50 mass % or more and 80 mass % or less, and the thermal conductivity of the adhesive layer can be further improved.
[0047] If the adhesive layer 4 contains a large amount of filler, the filler is likely to aggregate when the uncured resin material (adhesive) and the filler are kneaded, making it difficult to disperse the filler in the resin. To promote dispersion of the filler during kneading, the filler is preferably spherical rather than plate-like or fibrous.
[0048] In order to facilitate dispersion of the filler during kneading, the filler preferably has a bimodal particle size distribution.
[0049] The shape of the filler and the bimodal particle size distribution of the filler can be confirmed by the following method.
[0050] First, the electrostatic chuck member 2 or the base 3 is peeled off from the electrostatic chuck device 1 to expose the adhesive layer 4, and the surface of the exposed adhesive layer 4 is flattened by ion milling. An SEM image of the cross section is taken, and the particle diameter of each of the multiple fillers contained in the image is measured by image analysis. The particle diameter of the filler can be determined by analysis using image analysis software attached to the SEM.
[0051] The magnification of the SEM image is not limited as long as it allows measurement of the particle diameter of the filler contained in the adhesive layer 4, but it is preferable that at least 200 fillers are included in one visual field of the SEM image. The magnification of the SEM image is preferably, for example, 100 to 5000 times.
[0052] The shape of the filler (plate-like, fibrous, spherical) contained in the SEM image is confirmed from the obtained measured values.
[0053] In addition, the particle size distribution of the filler contained in the SEM image is obtained from the obtained measured values, and it is confirmed whether or not the particle size distribution is bimodal.
[0054] In this embodiment, the filler being "bimodal" means that there are two or more, preferably two, peaks showing maximum values in the particle size distribution obtained by the above method. In addition to the above method, whether the filler used as the material of the electrostatic chuck device 1 is bimodal may be determined by measuring the particle size distribution of the filler by a known laser diffraction scattering method.
[0055] The average particle diameter of the thermally conductive filler contained in the adhesive layer 4 is preferably 1 / 2 or less, and more preferably 1 / 2000 or more and 1 / 2 or less, of the thickness of the adhesive layer 4. When the average particle diameter of the thermally conductive filler is 1 μm or more and 100 μm or less, the thickness of the adhesive layer 4 is preferably 2 μm or more and 200 μm or less. Setting the thickness of the adhesive layer 4 in this manner makes it easier to form the adhesive layer 4 containing the filler to a uniform thickness, and can reduce cooling unevenness (improve thermal uniformity).
[0056] The average particle size of the filler can be determined by image analysis of the above-mentioned SEM image.
[0057] Such adhesive layer 4 preferably has a thermal conductivity of 0.3 W / mK or more, and more preferably has a thermal conductivity of 1.0 W / mK or more. When adhesive layer 4 has such a thermal conductivity, heat can be appropriately transferred from electrostatic chuck member 2 to base 3, and the entire apparatus can be appropriately cooled.
[0058] Moreover, the adhesive layer 4 preferably has an elastic modulus of 10,000 MPa or less, and more preferably has an elastic modulus of 1,000 MPa or less at 25° C. When the electrostatic chuck device 1 is used in a plasma process and heating and cooling are repeated, the adhesive layer 4 may peel off at the interface due to internal stress caused by the difference in thermal expansion between the electrostatic chuck member 2 and the base 3. In contrast, when the adhesive layer 4 has the above elastic modulus, the adhesive layer 4 can relieve the internal stress and suppress peeling.
[0059] The thermal conductivity and elastic modulus can be controlled by adjusting the amount of filler added. Tables 1 and 2 below show the thermal conductivity, elastic modulus, and the presence or absence of peeling after bonding of the MMC base (SiC 82 volume %, Si 18 volume %) / ceramic material (Al2O3-SiC) when each filler is added to the silicone resin.
[0060] [Table 1]
[0061] [Table 2]
[0062] The adhesive layer 4 may be formed by sandwiching a liquid adhesive between the electrostatic chuck member 2 and the base 3 and curing the adhesive, or may be formed by sandwiching a sheet-like or film-like adhesive between the electrostatic chuck member 2 and the base 3.
[0063] When the material of the adhesive layer 4 is a liquid adhesive, the viscosity of the adhesive is preferably 500 Pa·s or less.
[0064] As described above, when the amount of filler contained in the adhesive layer 4 increases, the adhesive strength between the adhesive layer 4 and the base 3 is likely to decrease. Therefore, it is preferable that a primer layer is formed on the surface of the base 3 that contacts the adhesive layer 4.
[0065] The primer layer is made of an organosilicon compound having a functional group that reacts with the resin material (adhesive) that is the material of the adhesive layer 4, and an alkoxy group. Examples of the functional group include an epoxy group, a vinyl group, a methacryl group, and a mercapto group. The organosilicon compound has one or more alkoxy groups. The organosilicon compound may be a single molecule or a polymer. As such an organosilicon compound, a compound known as a material for a primer layer can be used.
[0066] When such an organosilicon compound is applied to the surface of the base 3, the alkoxy group of the organosilicon compound reacts with the surface of the base 3 to form a bond. Also, the functional group of the organosilicon compound reacts with the adhesive to form a bond. As a result, when the primer layer is formed, a higher adhesive strength is generated between the adhesive layer 4 and the base 3 compared to when there is no primer layer.
[0067] (Support plate) The support plate 5 supports the base 3 from the lower surface 3b of the base 3. The support plate 5 is made of a material having a higher Young's modulus than the material of the base 3. For example, the material of the support plate 5 may be any of metal, MMC, and ceramics. Among them, it is preferable to use a ceramic plate such as Al2O3 having a higher Young's modulus than the base 3 as the support plate 5.
[0068] The ceramics used for the support plate 5 is preferably the same as the material used for the electrostatic chuck member 2. Specific examples of ceramics include aluminum oxide and aluminum nitride. By using the same material for the support plate 5 and the electrostatic chuck member 2, the difference in thermal expansion coefficient between the support plate 5 and the electrostatic chuck member 2 can be reduced, and warping of the electrostatic chuck device 1A can be suppressed.
[0069] (insulator) The insulator 23 is inserted into the hole 17 and assembled to the base 3. That is, the insulator 23 functions as an insertion part that is inserted into the hole 17. The insulator 23 is tubular and extends in the vertical direction (stacking direction). The power supply terminal 16 is disposed inside the insulator 23. The outer peripheral surface of the insulator 23 is joined to the inner surface of the hole 17 using a joining means such as adhesive. The insulator 23 insulates the metal base 3 from the power supply terminal 16.
[0070] The insulator 23 is made of, for example, ceramic. That is, the insulator 23 is made of an insulating material. This allows the insulator 23 to prevent the gas introduction hole from becoming a starting point of abnormal discharge. The insulator 23 has durability against plasma. As the ceramics constituting the insulator 23, ceramics containing one or more types selected from AlN, Al2O3, Si3N4, zirconium oxide (ZrO2), sialon, boron nitride (BN), and SiC can be used.
[0071] An end face (hereinafter, upper end face 23a) on the upper side (one side in the stacking direction) of the insulator 23 abuts against the electrostatic chuck member 2 or is disposed adjacent to the electrostatic chuck member with an insulating adhesive interposed therebetween.
[0072] (Power supply terminal) The power supply terminal 16 extends downward from the chucking electrode 13. The power supply terminal 16 is connected to an external power source 21. The power source 21 applies a voltage to the chucking electrode 13. The number, shape, etc. of the power supply terminals 16 are determined depending on the type of the chucking electrode 13, i.e., whether it is a monopolar type or a bipolar type.
[0073] The power supply terminal 16 passes through a first hole 17a in the dielectric substrate 11, a second hole 17b in the adhesive layer 4, and a third hole 17c in the support plate 5. The first hole 17a is provided in a portion of the dielectric substrate 11 below the attraction electrode 13.
[0074] The first hole 17a, the second hole 17b, and the third hole 17c are each circular when viewed from the stacking direction. The first hole 17a, the second hole 17b, and the third hole 17c are in communication with the hole 17 of the base 3.
[0075] The inner circumferential surfaces of the first hole 17a, the second hole 17b, and the third hole 17c are continuous with the inner circumferential surface of the insulator 23 when viewed from the stacking direction. The inner diameters of the first hole 17a, the second hole 17b, and the third hole 17c are approximately equal to the inner diameter of the insulator 23 and slightly larger than the outer diameter of the power supply terminal 16.
[0076] According to the electrostatic chuck device having the above-mentioned configuration, a novel electrostatic chuck device using a base made of MMC can be provided.
[0077] Although the preferred embodiment of the present invention has been described above with reference to the accompanying drawings, the present invention is not limited to the above embodiment. The shapes and combinations of the components shown in the above embodiment are merely examples, and various modifications can be made based on design requirements, etc., without departing from the spirit of the present invention. [Explanation of symbols]
[0078] 1A...electrostatic chuck device, 2...electrostatic chuck member, 3...base, 4...adhesive layer
Claims
1. an electrostatic chuck member made of a ceramic material; A base made of a metal matrix composite material; an adhesive layer that adheres the electrostatic chuck member and the base, The adhesive layer includes a resin material and a thermally conductive filler, an absolute value of a difference in thermal expansion coefficient between the ceramic material and the metal matrix composite material is 10 ppm / K or less; The adhesive layer has a content of the thermally conductive filler of 50% by mass or more and 80% by mass or less.
2. The electrostatic chuck device according to claim 1 , wherein the thermally conductive filler is spherical.
3. 3. The electrostatic chuck device according to claim 1, wherein the thermally conductive filler has a bimodal particle size distribution.
4. 3. The electrostatic chuck device according to claim 1, wherein an average particle diameter of the thermally conductive filler is equal to or smaller than half the thickness of the adhesive layer.
5. A primer layer is formed on a surface of the base that contacts the adhesive layer, 3. The electrostatic chuck device according to claim 1, wherein the primer layer is made of an organosilicon compound having an alkoxy group and a functional group that reacts with the resin material.
6. 3. The electrostatic chuck device according to claim 1, wherein the metal matrix composite material contains 75 volume % or more of silicon carbide and 1 volume % or more and 25 volume % or less of Al, Si, or Mg, when the entirety of the metal matrix composite material is taken as 100 volume %.
Citation Information
Patent Citations
Wafer holding device
JP1999163109A